Anatomic features of interest in women at risk of cardiac exposure from whole breast radiotherapy. Issue 3 (June 2015) - Lee, Grace; Rosewall, Tara; Fyles, Anthony; Harnett, Nicole; Dinniwell, Robert E.
Abstract Background and purpose Left-sided breast radiotherapy (RT) can result in cardiac exposure. This study aims to identify predictive anatomic features in women requiring breath-hold (RTBH) for cardiac sparing during adjuvant whole breast RT. Material and methods We retrospectively reviewed free-breathing (FB) CT scans of 80 women previously treated with left-sided breast RT. Unfavourable cardiac anatomy was defined as the number of consecutive axial CT slices (2 mm) in which the anterior chest wall contacted the heart (ContactHeart) or left ventricle (ContactLV). The sternal angle and Haller Index (HI) were used to measure chest concavity. Position and volume of post-operative cavity was also quantified. Results Heart mean dose (Dmean) was strongly correlated with ContactLV (r = 0.625, p < 0.001) and ContactHeart (r = 0.524, p < 0.001) but not significantly correlated with tumor size, cavity volume, heart volume, cavity distance to chest wall, sternal angle, or HI. ROC analysis of ContactHeart was most predictive of the need for breath-hold (RTBH) technique [Area Under Curve = 0.815 (SE: 0.048; 95% CI: 0.721–0.91)] and ⩾25 ContactHeart CT slices predicted for heart Dmean ⩾1.7 Gy (68% sensitivity and 82% specificity). Conclusion ContactHeart on FB CT of ⩾25 axial slices (2 mm), ⩾50 mm of para-sagittal heart contact, was predictive of higher heart Dmean and suggest a potential need for RTBH.